Rare Benign Median Nerve Angiogenetic Lipofibromatous Hamartoma: A Case Report - Mruthyunjaya, Talak Doddabasappa; Ugrappa, Harish; Sanchi, Bharathkrishna; Kumar, Akash (Scripta Medica, 2023)
Only a few cases of lipofibromatous hamartoma (LFH) of the median nerve have been described in the literature. LFH is a rare and low growing benign fibro-fatty tumour. It is characterised by the proliferation of mature adipocytes within the epineurium and the perineurium of the peripheral nerves. The median nerve is most frequently affected in the upper extremities. Carpal tunnel syndrome, paraesthesia, numbness and pain are frequently the results of involvement of the median nerve. In presented case, in addition to fibrolipoma, there was also new blood vessel formation noted, which was attributed to the chronicity of the lesion. Diagnosis was missed by ultrasound and MRI due to the presence of blood vessels. Histopathological diagnosis was confirmed. Surgical treatment with carpal tunnel release and neurolysis were performed. This resulted in favourable outcome in 3 months.